miR-433 Inhibits Neuronal Growth and Promotes Autophagy in Mouse Hippocampal HT-22 Cell Line - Xu, Chunli; Bai, Qingke; Wang, Chen; Meng, Qiuyu; Gu, Yuming; Wang, Qiwei; Xu, Wenjie; Han, Ying; Qin, Yong; Jia, Song; Zhang, Junfang; Xu, Jie; et al. (Frontiers in Pharmacology, 2020)
Background: MicroRNAs (miRNAs) have an increasing functional role in some neurodegenerative diseases. Autophagy, the degradation of bulk protein in the cytoplasm, is the quality control function of protein and has a protective role in the survival of neural cells. miR-433 may play a regulatory role in neurodegenerative diseases. Many aspects underlying the mechanism of miR-433 in neural development and neurodegeneration are not clear. Methods: In this study, we established stable cell lines expressing miR-433 by infecting mouse hippocampal neural cell line (HT-22) cells with rLV-miR-433 and the control rLV-miR. Pre-miR-433 expression was analyzed using polymerase chain reaction (PCR). Mature miR-433 expression was measured using quantitative PCR (qPCR). The effect of miR-433 overexpression on cell proliferation was determined using a CCK-8 assay and flow cytometry. RNA interference was used to analyze the function of Cdk12 in mediating the effect of miR-433 on cell proliferation. The effect of miR-433 overexpression on cell apoptosis was determined by flow cytometry. Autophagy-related genes Atg4a, LC3B, and Beclin-1 were determined using qPCR, western blot, or immunofluorescence. In addition, RNA interference was used to analyze the effect of Atg4a on the induction of autophagy. TargetScan 7.2 was used to predict the target genes of miR-433 and Smad9 was determined using qPCR. Results: Our results indicated that miR-433 increased the expression of Atg4a and induced autophagy by increasing the expression of LC3B-Ⅱ and Beclin-1 in an Atg4a-dependent manner. In addition, miR-433 upregulated the expression of Cdk12 and inhibited cell proliferation in a Cdk12-dependent manner and promoted apoptosis in HT-22 cells under the treatment of 10-hydroxycamptothecin. Conclusion: The results of our study suggest that miR-433 may regulate neuronal growth by promoting autophagy and attenuating cell proliferation. This might be a potential therapeutic intervention in neurodegenerative diseases.